Physical activity and sedentary behaviour in Bangladesh: a systematic scoping review. (February 2020) - Uddin, R.; Hasan, M.; Saif-Ur-Rahman, K.M.; Mandic, S.; Khan, A.
Abstract: Objectives: Lack of physical activity (PA) contributes to increasing prevalence of non-communicable diseases (NCDs) globally. However, little is known about PA and sedentary behaviour (SB) among populations in low- and middle-income countries (LMICs). This systematic review examined prevalence of PA and SB in Bangladesh. Study design: Systematic review of the literature. Methods: A systematic electronic search in eight databases and a manual search of retrieved articles' references were conducted. Original research conducted in Bangladesh with PA- and/or SB-related outcome(s) were included. Results: Out of 1, 162 retrieved titles, 33 articles (32 cross-sectional and one case–control study) met the inclusion criteria. Twenty-nine studies were with healthy populations: adults (n = 19); children and adolescents (n = 7); and children, adolescents and adults (n = 3). Five studies used nationally representative samples of adults and one of adolescents. Most studies (n = 26) assessed PA only; three only SB, and four both PA and SB. All studies used self-reported measures. Among healthy adults, prevalence of insufficient PA ranged from 5% to 83%. Occupational and transport-related PA contributed the most towards total PA with negligible contribution of recreational PA. Among children and adolescents, the prevalence of insufficient PA ranged between 20% and 67%. Females engaged in less PA compared to males. Limited evidence currently exists about the prevalence of SB, especially among adults. Conclusions: PA and SB research has received little attention in Bangladesh. Critical knowledge gaps identified in this review should be taken into account when designing new research and programmes in Bangladesh and other LMICs with similar socio-economic and cultural settings. Highlights: Physical activity research is in its infancy in Bangladesh. Prevalence of physical inactivity varied greatly across the studies. Females were less active than males. Participation in recreational physical activity was low. Sedentary behaviour has received little attention.